Impact of maternal visceral leishmaniasis on sex-specific immune responses and pathogenesis in offspring following homologous infections - Mizobuchi, Haruka; Sanjoba, Chizu; Goto, Yasuyuki (Frontiers in Immunology, 2026)
Leishmania donovani (Ld), the etiological agent of visceral leishmaniasis, has recently been implicated in vertical transmission, raising concerns about the potential impact of maternal infection on offspring immunity and disease susceptibility. Despite this, the effects of maternal Ld infection on the offspring’s immune responses and pathogenesis upon homologous infection remain largely uncharacterized. In this study, we investigated the influence of maternal Ld infection on disease outcomes in offspring by challenging offspring born to chronically infected female mice with homologous Ld parasites. Although persistent infection or acquired immune memory was not detected in offspring postnatally, distinct sex-dependent pathological outcomes were observed following challenge. Male offspring exhibited exacerbated erythrophagocytosis by splenic macrophages, leading to marked anemia irrespective of splenic parasite burden. In contrast, female offspring showed aggravated hepatic parasitic proliferation, inflammatory infiltration, granuloma formation, and extensive liver damage. These findings suggest that maternal Ld infection induces long-lasting, sex-specific alterations in the offspring’s immune system, particularly affecting macrophage function. This study provides the first evidence that maternal Ld infection differentially shapes the offspring’s immunopathological responses to homologous infection in a sex-dependent manner, offering novel insights for risk assessment and the development of sex-informed strategies for disease prevention.